Les écoles au Sénégal : de l’enseignement officiel au daara, les modèles et leurs répliques - Jean-Émile Charlier (Cahiers de la Recherche sur l'Education et les Savoirs)
A survey carried out in Senegal among political, cultural, economic and religious leaders has highlighted very different conceptions of the human achievement and the role of the school. The state education remains the reference, but its weak effectiveness and its politization are often criticized. The catholic schools are unanimously appreciated, they combine formalization and effectiveness. The koranic schools are at a long distance of the formal ones. They have the one objective to teach religion. Some of their teaching models are very disputed because they are based on symbolic and physical violences. In this context, the 2002 law introducing religious teaching into the official schools would modify the balance of power in favour of the religion teachers.